Design of an Integrated Cascade Framework for the Graduation Program of Bank BRI Microcredit Debtors - Lukmanul Khakim; Hardy R. Hermawan; Tiolina Evi N. Pardede; R. Eko Indrajit (Jambura Science of Management, 2026)
Purpose: This study aims to develop an adaptive change management framework to enhance the capacity of microcredit borrowers while strengthening the credit risk management model at Bank Rakyat Indonesia (BRI). Currently, BRI faces significant challenges in managing credit risk quality within the micro segment, which accounts for approximately 37.1% of the total loan portfolio. Despite its strategic role in promoting financial inclusion and economic empowerment, this segment continues to exhibit a relatively higher Non-Performing Loan (NPL) ratio compared to other segments. This condition results in substantial provisioning burdens and increases the potential for moral hazard, driven by interest rate subsidies that are not supported by an effective mechanism for debtor graduation.Design/Methodology/Approach: This study employs a qualitative approach, employing thematic analysis, and synthesizes the ADKAR model and the Integrative Change Model (ICM) into an original framework termed the Integrated Cascade Framework (ICF). The ICF framework integrates change simultaneously across three layers: strategic–governance, operational–organizational, and ecosystem–debtor behavior.Findings: The findings indicate that this integration can align the corporate risk appetite with tangible changes in debtor behavior toward graduation. The implementation of the Integrated Cascade Framework (ICF) is expected to foster a more sustainable, well-controlled, and adequate microcredit distribution pattern, thereby significantly enhancing national productive capacity.